1991
DOI: 10.1093/ajcn/53.4.1042s
|View full text |Cite
|
Sign up to set email alerts
|

Dietary tocotrienols reduce concentrations of plasma cholesterol, apolipoprotein B, thromboxane B2, and platelet factor 4 in pigs with inherited hyperlipemias

Abstract: Normolipemic and genetically hypercholesterolemic pigs of defined lipoprotein genotype were fed a standard diet supplemented with 50 micrograms/g tocotrienol-rich fraction (TRF) isolated from palm oil. Hypercholesterolemic pigs fed the TRF supplement showed a 44% decrease in total serum cholesterol, a 60% decrease in low-density-lipoprotein (LDL)-cholesterol, and significant decreases in levels of apolipoprotein B (26%), thromboxane-B2 (41%), and platelet factor 4 (PF4; 29%). The declines in thromboxane B2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(75 citation statements)
references
References 15 publications
9
65
0
1
Order By: Relevance
“…One study suggested that tocopherol has a negative impact on the lipid lowering property of tocotrienols (Qureshi et al, 1995), via its stimulating effect on HMG-CoA reductase, the rate-limiting enzyme in the cholesterol synthesis pathway, thus attenuating the inhibitory effect exerted by tocotrienols (Qureshi et al, 1996). It was determined that in a mixed preparation of tocotrienol and tocopherol, 20% or more of the latter leads to attenuation of the former's hypocholesterolaemic effects (Qureshi et al, 1995;Qureshi et al, 1991). …”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that tocopherol has a negative impact on the lipid lowering property of tocotrienols (Qureshi et al, 1995), via its stimulating effect on HMG-CoA reductase, the rate-limiting enzyme in the cholesterol synthesis pathway, thus attenuating the inhibitory effect exerted by tocotrienols (Qureshi et al, 1996). It was determined that in a mixed preparation of tocotrienol and tocopherol, 20% or more of the latter leads to attenuation of the former's hypocholesterolaemic effects (Qureshi et al, 1995;Qureshi et al, 1991). …”
Section: Discussionmentioning
confidence: 99%
“…Evidence that the Tocotrienol-Rich Fraction (TRF) of palm oil may indeed lower plasma cholesterol in mammals came from a study of normolipemic and genetically hypercholesterolemic pigs of defined lipoprotein genotype. 40 The pigs were fed a standard diet supplemented with 50 micrograms/g TRF isolated from palm oil. Hypercholesterolemic pigs fed the TRF supplement showed a 44% decrease in total serum cholesterol, a 60% decrease in LDL-cholesterol, and significant decreases in levels of apolipoprotein B (26%), thromboxane-B2 (41%), and platelet factor 4 (PF4; 29%).…”
Section: Hypercholesterolemic Effectsmentioning
confidence: 99%
“…Theriault et al (1999) studied the effect of c-tocotrienol on apoB synthesis, degradation, and secretion in human hepatocellularcarcinoma cell line (HepG2) which revealed that the presence of c-tocotrienol in the cells stimulates apoB degradation, and it is speculated that the lack of cholesterol availability reduces the number of secreted apoB-containing lipoprotein particles by limiting translocation of apoB into the endoplasmic reticulum lumen. Several epidemiological studies have shown that tocotrienols reduce the atherogenic apoB plasma levels significantly by 10-15% (Qureshi et al 1991a(Qureshi et al , 1995Qureshi and Peterson 2001). A case-controlled study (Qureshi et al 1995) showed that a novel tocotrienol-rich fraction (TRF) from specially processed rice bran oil enriched with didesmethyl-tocotrienol, an isoform of tocotrienols with no methyl groups on the chromanol ring was shown to decrease plasma lipoprotein ''a'' levels by 17%.…”
Section: Lipid-lowering Property Of Tocotrienols In Cardioprotectionmentioning
confidence: 99%
“…Qureshi et al (1996) observed that plasma cholesterol lowering by tocotrienol-rich extracts in chicken and rat was associated with decreased levels of hepatic HMG-CoA reductase activity. Hypercholesterolemic pigs fed the tocotrienol-rich fraction supplement showed a 44% decrease in total serum cholesterol, a 60% decrease in LDL cholesterol, and significant decreases in levels of apolipoprotein B (26%), thromboxane B2 (41%), and platelet factor 4 (PF4; 29%) (Qureshi et al 1991a). In isolated human liver cells, a-tocotrienol (10 mM for 4 h) inhibited cholesterol synthesis by 32%.…”
Section: Lipid-lowering Property Of Tocotrienols In Cardioprotectionmentioning
confidence: 99%